"Even the fowl has feelings": access to HIV information and services among persons with disabilities in Ghana, Uganda, and Zambia. Issue 3 (30th January 2020) - Schenk, Katie D.; Tun, Waimar; Sheehy, Meredith; Okal, Jerry; Kuffour, Emmanuel; Moono, Grimond; Mutale, Felix; Kyeremaa, Rita; Ngirabakunzi, Edson; Amanyeiwe, Ugochukwu; Leclerc-Madlala, Suzanne
Abstract: Background: Persons with disabilities have often been overlooked in the context of HIV and AIDS risk prevention and service provision. This paper explores access to and use of HIV information and services among persons with disabilities. Methods: We conducted a multi-country qualitative research study at urban and rural sites in Uganda, Zambia, and Ghana: three countries selected to exemplify different stages of the HIV response to persons with disabilities. We conducted key informant interviews with government officials and service providers, and focus group discussions with persons with disabilities and caregivers. Research methods were designed to promote active, meaningful participation from persons with disabilities, under the guidance of local stakeholder advisors. Results: Persons with disabilities emphatically challenged the common assumption that persons with disabilities are not sexually active, pointing out that this assumption denies their rights and – by denying their circumstances – leaves them vulnerable to abuse. Among persons with disabilities, knowledge about HIV was limited and attitudes towards HIV services were frequently based upon misinformation and stigmatising cultural beliefs; associated with illiteracy especially in rural areas, and rendering people with intellectual and developmental disability especially vulnerable. Multiple overlapping layers of stigma towards persons with disabilities (including internalised self-stigma and stigma associated with gender and abuse) have compounded each other to contribute to social isolation and impediments to accessing HIV information and services. Participants suggested approaches to HIV education outreach that emphasise the importance of sharing responsibility, promoting peer leadership, and increasing the active, visible participation of persons with disabilities in intervention activities, in order to make sure that accurate information reflecting the vulnerabilities of persons with disabilities is accessible to people of all levels of education. Fundamental change to improve the skills and attitudes of healthcare providers and raise their sensitivity towards persons with disabilities (including recognising multiple layers of stigma) will be critical to the ability of HIV service organisations to implement programs that are accessible to and inclusive of persons with disabilities. Discussion: We suggest practical steps towards improving HIV service accessibility and utilisation for persons with disabilities, particularly emphasising the power of community responsibility and support; including acknowledging compounded stigma, addressing attitudinal barriers, promoting participatory responses, building political will and generating high-quality evidence to drive the continuing response. Conclusions: HIV service providers and rehabilitation professionals alike must recognise the two-way relationship between HIV and disability, and their multiple overlapping vulnerabilities and stigmas. Persons with disabilities demand recognition through practical steps to improve HIV service accessibility and utilisation in a manner that recognises their vulnerability and facilitates retention in care and adherence to treatment. In order to promote lasting change, interventions must look beyond the service delivery context and take into account the living circumstances of individuals and communities affected by HIV and disability. Implications for Rehabilitation: Persons with disabilities are vulnerable to HIV infection but have historically been excluded from HIV and AIDS services, including prevention education, testing, treatment, care and support. Fundamental change is needed to address practical and attitudinal barriers to access, including provider training. Rehabilitation professionals and HIV service providers alike must acknowledge the two-way relationship between HIV and disability: people with disability are vulnerable to HIV infection; people with HIV are increasingly becoming disabled. Peer participation by persons with disabilities in the design and implementation of HIV services is crucial to increasing accessibility. Addressing political will (through the National Strategic Plan for HIV) is crucial to ensuring long-term sustainable change in recognizing and responding to the heightened vulnerability of people with disability to HIV.